PENGARUH KUALITAS WEBSITE DAN E-SERVICE QUALITY TERHADAP IMPULSIVE BUYING KONSUMEN TIKTOK SHOP: STUDI PADA MAHASISWA MANAJEMEN FEB UNIVERSITAS PALANGKA RAYA - Simbolon, Seylafani; Meitiana, Meitiana; Sukmani, Meylinda; Pakpahan, Aston (Penerbit Lafadz Jaya, 2026)
The rapid growth of the digital economy and the high usage of TikTok Shop in Indonesia have significantly influenced consumer behavior, particularly the increase in impulsive buying, especially among university students. This phenomenon is influenced by several factors, including website quality and e-service quality provided by the platform. This study aims to analyze the effect of website quality and e-service quality on impulsive buying behavior of TikTok Shop consumers among Management students at the Faculty of Economics and Business, University of Palangka Raya. This research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 96 respondents selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results are expected to indicate that website quality significantly affects impulsive buying, e-service quality significantly affects impulsive buying, and both website quality and e-service quality simultaneously have a significant effect on impulsive buying behavior of TikTok Shop consumers. This study is expected to contribute theoretically to the development of digital consumer behavior studies and provide practical insights for business practitioners and social commerce platforms in designing effective and responsible online shopping experiences, particularly for the student segment.